Influence of soil properties on N2O and CO2 emissions from excreta deposited on tropical pastures in Kenya - Yuhao Zhu; Merbold, Lutz; Leitner, Sonja; Longlong Xia; Pelster, David E.; Diaz Pines, Eugenio; Abwanda, Sheila O.; Mutuo, Paul M.; Butterbach-Bahl, Klaus (Elsevier, 2020)
Urine and dung patches deposited by grazing cattle on grassland are an important source of nitrous oxide (N2O). While a number of studies have investigated the effects of excreta on soil N2O fluxes in developed economies and in China, observations in sub-Saharan Africa (SSA) are scarce. Moreover, the effects of soil properties (e.g. pH or texture) on N2O emissions from excreta patches have hardly been studied. In this study we investigated the importance of soil properties on N2O and carbon dioxide (CO2) emissions from cattle excreta (dung, urine, and manure [dung + urine]) for five typical tropical soils in Kenya. For this, intact soil cores were translocated from Western Kenya (Nandi county) to Nairobi, where N2O and CO2 fluxes were measured over four individual periods (two during dry seasons and two during wet seasons). Fluxes were measured for between 25 and 73 days following surface application of excreta, depending on how quickly emissions returned to baseline. Both dung and manure applications led to increased CO2 and N2O fluxes during both dry and wet seasons. On average, the N2O emission factor (EF) for manure was higher than for dung. The EFs during the wet season were higher for both the dung (0.12%) and urine (0.50%) compared to the dry season EFs (0.01% and 0.07% for dung and urine respectively). Soil type had no measurable effect on N2O and CO2 emissions for either dung or manure application. In contrast, soil clay content was negatively (P < 0.05) and pH positively (P < 0.05) correlated with N2O emissions after urine application. Assuming an excreta-N ratio of dung to urine of 66:34, as evidenced in earlier studies for SSA, and averaging across all treatments and soils, we calculated a cattle excreta N2O EF of 0.14%, which is one magnitude lower than the IPCC default N2O EF of 2%. Our results call for a revision of the IPCC guidelines for calculating N2O emissions from excreta deposition on tropical rangelands.